SUFI PRACTICES OF THE QADIRIYYA ORDER OF CHECHENS AND INGUSH IN KAZAKHSTAN: HISTORY AND MODERNITY - Albogacieva, Makka Sultan-Gireevna (History, Archeology and Ethnography of the Caucasus, 2024)
The emergence of the Qadiriyya order in Kazakhstan, practiced by the Chechens and Ingush, is inextricably linked to the tragic events that befell these Caucasian peoples during the Great Patriotic War. Falsely accused of collaborating with the Nazis, the Ingush, Chechens, Balkars, Karachays, Kalmyks, and other ethnic groups were forcibly deported from their ancestral lands to Central Asia. A second wave of Ingush and Chechen migration to Kazakhstan occurred during the Ossetian-Ingush conflict of 1992 and the subsequent Chechen Wars. Despite their displacement from their homeland, these groups retained their distinctive ethno-cultural features, with Sufi spiritual practices occupying a prominent position among these preserved traditions. This article aims to demonstrate the establishment of Qadiriyya in Kazakhstan and examine the unique characteristics of this tariqah’s existence in a new environment for the Ingush and Chechens. The main body of the article is divided into several thematic sections: deportation, reasons for the Ingush and Chechens’ decision not to return to their homeland, and Qadiriyya communities in Kazakhstan. This structure allows for a comprehensive exploration of the role and significance of Sufi practices in maintaining both religious and ethnic identity within Kazakhstan’s multi-ethnic and multi-confessional society. The study found that Sufism, as in the Caucasus, remains an integral part of the Ingush and Chechen spiritual world in their new region of residence and resists cultural assimilation with other spiritual practices prevalent in Kazakhstani society. The study employs contemporary methods of historical and ethnological analysis, which are essential for comprehending the significance of cultural phenomena and providing a detailed examination of Islam’s manifestation in Kazakhstan.
Keywords: Ingush; Chechens; Kazakhstan; Islam; Sufism; Qadiriyya; dhikr; ritual